Literature and Revolution as an Avant-garde Heritage. Round Table on the Faculty of Humanities and Social Sciences in Zagreb - Protrka Štimec, Marina (Poznańskie Studia Slawistyczne, 2020)
The text summarizes and reviews the round table organized on the 19th September 2019 at the Faculty of Humanities and Social Sciences in Zagreb with the main goal to investigate the methodological and thematic approaches to the avant-garde related to the concept of revolution. The scientists from Zagreb and Belgrade, Tatjana Jukić, Predrag Brebanović, Danijela Lugarić and Branislav Oblučar, presented their contributions to debate around the above-mentioned themes. Literature as well as revolution were examined in the theoretical and historical context of the avant-garde. Public debate showed that these issues have been still sparking vivid interest in the academic, artistic and intellectual world. The round table was organized as part of the project Literary Revolutions established by the Croatian science foundation 2018-017020.